Flanking transmission of metal stud walls with different junction details. (October 2016) - Späh, Moritz; Weber, Lutz
Abstract: Measurements of the normalised flanking sound level difference of different gypsum board flanking walls are reported. Results of a "standard" wall construction confirmed some results of the current draft standard of DIN 4109. Different constructions with various junction details and different wall constructions are described and measurement results are presented. By additional measurements on the walls, a prediction model for the weighted flanking level difference is suggested, based on the methodology of EN 12354. For the flanking transmission prediction of path Ff, three transmission paths are proposed. The model gives good agreement between calculated and measured weighted flanking level difference except for the case where the transmission along the inner lining of the flanking wall is dominant. In this case the prediction underestimates measurements by up to 7 dB.